Impact of intravenous thrombolysis and emergent carotid stenting on reperfusion and clinical outcomes in patients with acute stroke with tandem lesion treated with thrombectomy: a collaborative pooled analysis. (16th April 2018) - Gory, B.; Haussen, D. C.; Piotin, M.; Steglich‐Arnholm, H.; Holtmannspötter, M.; Labreuche, J.; Kyheng, M.; Taschner, C.; Eiden, S.; Nogueira, R. G.; Papanagiotou, P.; Boutchakova, M.; et al.
Abstract : Background and purpose: Tandem anterior circulation lesions in the setting of acute ischemic stroke (AIS) are a complex endovascular situation that has not been specifically addressed in trials. We determined the predictors of successful reperfusion and good clinical outcome at 90 days after mechanical thrombectomy (MT) in patients with AIS with tandem lesions in a pooled collaborative study. Methods: This was a retrospective analysis of consecutive patients presenting to 18 comprehensive stroke centers with AIS due to tandem lesion of the anterior circulation who underwent MT. Results: A total of 395 patients were included. Successful reperfusion (modified thrombolysis in cerebral infarction score 2b–3) was achieved in 76.7%. At 90 days, 52.2% achieved a good outcome (modified Rankin Scale score 0–2), 13.8% suffered a parenchymal hematoma and 13.2% were dead. Lower National Institutes of Health Stroke Scale score [odds ratio (OR), 1.26; 95% confidence intervals (CI), 1.07–1.48, P = 0.004], Alberta Stroke Program Early CT Score ≥7 (OR, 2.00; 95% CI, 1.07–3.43, P = 0.011), intravenous thrombolysis (OR, 1.47; 95% CI, 1.01–2.12, P = 0.042) and stenting of the extracranial carotid lesion (OR, 1.63; 95% CI, 1.04–2;53, P = 0.030) were independently associated with successful reperfusion. Lower age (OR, 1.58; 95% CI, 1.26–1.97, P < 0.001), absence of hypercholesterolemia (OR, 1.77; 95% CI, 1.10–2.84, P = 0.018), lower National Institutes of Health Stroke Scale scores (OR, 2.04; 95% CI, 1.53–2.72, P < 0.001), Alberta Stroke Program Early CT Score ≥7 (OR, 2.75; 95% CI, 1.24–6.10, P = 0.013) and proximal middle cerebral artery occlusion (OR, 1.59; 95% CI, 1.03–2.44, P = 0.035) independently predicted a good 90‐day outcome. Conclusions: Intravenous thrombolysis and emergent stenting of the extracranial carotid lesion were predictors of a successful reperfusion after MT of patients with AIS with tandem lesion of the anterior circulation. Abstract : Clickhere to view the accompanying paper in this volume.